Nothing less than a creative triumph: a study of children admitted to hospital for serious somatic illness or injury and their experience of art therapy - Loreskär, Patricia; Binder, Per-Einar (Frontiers in Psychology, 2024)
Background: Hospitalization can be an extremely distressing experience for seriously ill and injured children. Art therapy has a well-established clinical history, and recent research has begun to demonstrate its effectiveness in somatic pediatric wards. Descriptive and statistical research indicates that art therapy can alleviate anxiety and fear, improve mood, and enhance communication among children, parents, and healthcare professionals. This study aims to enhance our understanding of the specific elements of art therapy that facilitate a connection with the healthier aspects of the self. Method: A total of 12 hospitalized children, aged 4-12, participated in an art therapy session led by a certified art therapist. Verbalizations during the sessions were recorded, and subsequent observations were synchronized with verbatim transcriptions of audio recordings.A reflexive thematic analysis was conducted to identify relevant patterns of meaning.Findings: The study identified four significant dimensions of the children's experiences during art therapy: 1) The child feels safe, 2) The child becomes a competent artist, bursting with creativity, 3) The healthy child emerges, 4) The child achieves something beyond its limits -a triumph Discussion: The active ingredients contributing to effective art therapy include the stimulation of creativity, guided art-making with scaffolding support, task variation, granting children control over the artistic process, encouragement of free expression, and the display of positive regard. This study also delves into the therapeutic alliance, emphasizing its role in facilitating children's learning, self-expression, concentration, and the creation of work they take pride in.Additionally, certain psychotherapy-like interactions, such as control-mastery dynamics, were slettet: their relationship to their art therapist, creative materials and the art they create slettet: Establishment of a trusting relationship between the child and the therapist slettet: Engagement in the art-making process, fostering a sense of creativity and competence, slettet: Pain and discomfort shifting to the background, and 4) The emergence of the "Healthy Child Within," taking a central role and resulting in a notable sense of triumph. ¶ observed. Nevertheless, more extensive research with larger sample sizes is required to draw broader conclusions.